(untitled) (Communications in Computational Physics, 2010)
We numerically simulate a photonics phenomenon of what we call intensity inversion between red and green fluorescence in oxyfluoride nanophase vitroceramics Er(1%)Yb(8%): FOV through the integration of whole fluorescence's theories. We found that it is essential to introduce a coefficient presenting the difference between the Stokes energy transfer and anti-Stokes energy transfer processes in nano-material when calculating the energy transfer rate. Under this consideration, and with the total crystallized volume ratio set to be 17.6%, the simulation results of the population probabilities values of all energy levels of Er3+ ion are coincident with the experimental result perfectly.